Pengaruh Celebrity Endorser, E-Advertisement, dan E-Service Quality Terhadap Keputusan Pembelian Goddesskin by Athena di Shopee - Rahmawaty, Putri; Hildayanti, Siti Komariah; Lazuarni, Shafiera (UNHI Press, 2025)
The shift in consumer behavior toward purchasing skincare products through e-commerce platforms presents challenges for companies in determining the most effective digital marketing strategies. This study aims to analyze the influence of celebrity endorsers, e-advertisement, and e-service quality on purchasing decisions, both partially and simultaneously. The research employed a descriptive quantitative method, with data collected through an online questionnaire. The population of this study consisted of consumers who had purchased Goddesskin by Athena products through the Official Online Store on Shopee, with a total sample of 140 respondents. Data analysis was carried out using multiple linear regression analysis. The results indicate that the three independent variables—celebrity endorsers, e-advertisement, and e-service quality—have a positive and significant effect on purchasing decisions. Simultaneously, these variables also contribute significantly to consumers’ decisions to purchase the product. These findings suggest that effective digital marketing strategies involving public figures, engaging online promotions, and quality online services can increase consumer purchasing tendencies for skincare products in the e-commerce environment.